Politisasi Kebijakan dalam Rancangan Undang-Undang Keamanan Nasional - Djuyandi, Yusa (Humaniora, 2014)
Discussion of the draft of National Security Act in the House of Representatives cannot be separated from the political charge. Politicization of policy formulation in the draft of National Security Act sometimes can lead to the policy distortion. The purpose of this study is to describe and analyze the policy politicization of National Security Act draft. This study revealed that from the aspect of ?all questions political questions?, the Parliament gives a political question in the framework of the process of policy control. In the second aspect, ?all issues political issues?, issues that arise and become a concern are issues which are considered threaten the human rights and democracy. In the third, ?all values political values?, the parliament is fighting for the human rights and democracy values. From the last aspect of ?all decisions political decisions?, the parliament political decision for not approving the draft, because it is not in favor with the agenda of reformation and democracy. This study concluded that the politicization of policy in the Draft Law is still considered normal. Politicization occurred because policy adoption involves the executive and the legislature, in the context of political checks and balances.